Multilevel metabolic and enzyme engineering enables efficient biosynthesis of cyanidin-3-O-glucoside from dihydroquercetin in Escherichia coli - Zhiyao Wang; Wei Xie; Ruichen Gao; Zezhong Tu; Wenyong Lou; Xiaoling Wu (Bioresource Technology, 2027)

A nonlinear constitutive model for fine sandstone considering freeze–thaw induced compaction and damage evolution - Qi Wu; Ruichen Luo; Bowen Li; Qinyan Qiu; Maiyong Jiang; Guan Rong (Bulletin of Engineering Geology and the Environment, 2026)

Dataset of China Kuroshio Extension Observatory (CKEO): Moored Buoy Observations in the Kuroshio–Oyashio Transition Zone - Zhaohui Chen; Yueqi Zhang; Ruichen Zhu; Zhongxiang Fan; Jia-Zhen Wang; Xin Ma; Guoqing Ren; Haiyuan Yang; Lixiao Xu; Xiaopei Lin; Lixin Wu (Advances in Atmospheric Sciences, 2026)
The Kuroshio–Oyashio Transition Zone (KOTZ) serves as a vital dynamic interface between the warm Kuroshio Extension and the cold Oyashio Current. However, severe sea conditions with strong ocean currents, winds and waves pose challenges for sustained in situ observations of both oceanic and atmospheric variables. This paper introduces the China Kuroshio Extension Observatory (CKEO), a moored observatory program designed for long-term observations in the KOTZ. We provide a dataset of meteorological and oceanographic properties, including sea surface wind, air temperature, atmospheric pressure, relative humidity, sea surface temperature, sea surface salinity, ocean currents in the upper 100 m, and temperature profile in the upper 500 m. The CKEO, which began operations in 2019, provides a continuous air–sea observational dataset of the KOTZ to the scientific community and advances the understanding of multiscale physical processes in this region.

Engineering the primary and second coordination sphere of metal-organic framework boosts the peroxidase-like activity - Xin Yuan; Xinghua Chen; Jun Xiong; Yifang Cao; Niya Ta; Ruichen Gao; Shuli Liu; Min-Hua Zong; Xiaoling Wu; Wen-Yong Lou (Chemical Engineering Journal, 2025)

Identification of active sites for formaldehyde oxidation on mesoporous Pt/CeO2 catalyst at ambient temperature and low humidity - Ruichen Wang; Chao Yu; Juanjuan Gong; Qingfa Su; Hui Chen; Canyan Yang; Shaodi Sun; Zhiwei Huang; Huazhen Shen; Huawang Zhao; Bihong Lv; Xiaomin Wu; et al. (Fuel, 2025)

Ratiometric fluorescent detection of protease activity in foods based on microwave-assisted synthesized casein-directed gold nanoclusters - Haoxing You; Jun Xiong; Ruichen Gao; Wen-Yong Lou; Xiaoling Wu (Food Chemistry, 2025)

Orbital lifetime design and optimization of CORBES based on lunisolar perturbation - Maojin Sun; Ruichen Xi; Chao Wei; Fan Wu; Li Deng (Advances in Space Research, 2025)

A multi-target and responsive nanoplatform (MM/ZnS/ATV) combining H2S and atorvastatin for enhanced atherosclerosis therapy - Yinhong Xie; Mengchen Chi; Ruichen Dong; Sui Wu; Jinming Yang; Qin Wang; Junying Chen; Yajun Weng (Chemical Engineering Journal, 2024)

Decades-long organic tea production is distinguished by N deficiency: Evidence from soil and tea δ15N data - Ruichen Shuang; Lijuan Du; Jinliang Shao; Yuping Tian; Di Wu; Fanqiao Meng (Science of The Total Environment, 2024)

Evaluating net primary productivity dynamics and their response to land-use change in the loess plateau after the 'Grain for Green' program - Ruichen Mao; Lutong Xing; Qiong Wu; Jinxi Song; Qi Li; Yongqing Long; Yuna Shi; Peng Huang; Qifang Zhang (Journal of Environmental Management, 2024)

Insectivorous birds are more sensitive to urban greenspace changes in Guangzhou city, China - Ruichen Wu; Qiang Zhang; Zezhou Hao; Le Li; Bingtao Gao; Jianrong Li; Xiaotian Liu; Chao Liao; Nancai Pei (Urban Forestry & Urban Greening, 2024)

Mechanistic insight into the catalytic CO oxidation and SO2 resistance over Mo-decorated Pt/TiO2 catalyst: The essential role of Mo - Chao Yu; Canyan Yang; Ruichen Wang; Geyu Dai; Hui Chen; Zhiwei Huang; Huawang Zhao; Zuoming Zhou; Xiaomin Wu; Guohua Jing (Chemical Engineering Journal, 2024)

Engineering stable Cu+-Cu0 sites and oxygen defects in boron-doped copper oxide for electrocatalytic reduction of CO2 to C2+ products - Canyan Yang; Ruichen Wang; Chao Yu; Jinhua Xiao; Zhiwei Huang; Bihong Lv; Huawang Zhao; Xiaomin Wu; Guohua Jing (Chemical Engineering Journal, 2024)

Triclocarban exposure aggravates dextran sulfate sodium-induced colitis by deteriorating the gut barrier function and microbial community in mice - Mengyu Qin; Hehua Lei; Yuchen Song; Mengjing Wu; Chuan Chen; Zheng Cao; Cui Zhang; Ruichen Du; Ce Zhang; Xian Wang; Limin Zhang (Food and Chemical Toxicology, 2023)

Pt single atoms and defect engineering of TiO2-nanosheet-assembled hierarchical spheres for efficient room-temperature HCHO oxidation - Xiaomin Wu; Shaodi Sun; Ruichen Wang; Zhiwei Huang; Huazheng Shen; Huawang Zhao; Guohua Jing (Journal of Hazardous Materials, 2023)

Araneose Ti3+ self-doping TiO2/SiO2 nanowires membrane for removal of aqueous MB under visible light irradiation - Zhao Gao; Hanpei Yang; Jingtao Mao; Li Kang; Ruichen Zhang; Siqi Chai; Junming Wu; Wei Li (Environmental Science and Pollution Research, 2020)